(untitled) (Research, Society and Development, 2023)
Strongly associated with obesity, non-alcoholic fatty liver disease (NAFLD) is characterized by ectopic deposition of hepatic fat that causes histopathological abnormalities with a high risk of morbidity and mortality. Individuals with morbid obesity are the most affected by the disease, and for these patients, bariatric surgery remains the best therapeutic option for sustained weight loss. The aim of this study is to compare Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (Sleeve) techniques and discuss their effects in the treatment of NAFLD. This is an integrative literature review based on the Virtual Health Library (VHL) and National Library of Medicine – National Institutes of Health (PUBMED) databases. The screening process had the following inclusion criteria: articles that answered the research question, in English, Portuguese and Spanish and published between 2018 and 2023. From this, a total of 16 studies were obtained. The discussion included four thematic axes: 1. Pathogenesis of NAFLD addressing the factors involved in liver dysfunction; 2. Limitations of conservative treatment, which includes lifestyle interventions and pharmacotherapy; 3. Effects of bariatric surgery on the stages of NAFLD, among them, the improvement of inflammation and hepatocellular ballooning. Finally, the comparison of the hepatic effects induced by the techniques, showing the best results.